(untitled) (Research, Society and Development, 2022)
Medicinal plants have been widely used for the treatment, prevention and cure of diseases, as they have been used for medicinal purposes by humanity since ancient times. Due to their therapeutic or toxic properties, they gained importance in popular and conventional medicine. Therefore, the present research aimed to evaluate, through in silico prediction, the toxicological parameters of Melissa officinalis L. in order to obtain new drug candidates from this species. It was a basic, experimental, cross-sectional, quantitative study carried out through the analysis of theoretical toxicity with a free admetSAR software. For the compound acetyl tributyl citrate, which for most parameters was not considered toxic, there is the possibility of being used alone as an antifungal, antibacterial, antileshimania and insecticide, since it belongs to the citral essential oil component. which is the majority present in M. officinallis. However, it is necessary that there is continuity of work using this species cultivated in the southern region of Tocantins, since it was verified a promising compound for future investigations in in vitro and in vivo tests, which may be a strong candidate for a new drug.